In vivo teratogenecity and anti-allergic of lignosus rhinoceros in an asthmatic robert model and their possible bioactive constituents - Abdullah, Nurul Asma (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Lignosus rhinoceros (L. rhinoceros) or locally known as Tiger's Milk mushroom, is traditionally used in the treatment of various diseases including asthma by indigenous communities in Malaysia. This study investigated volatile constituents of L. rhinocerus using gas chromatography mass spectrometry (GC-MS), teratogenic and male fertility, immunomodulatory properties and anti-asthmatic effects of L. rhinocerus in animal models. Sequential extractions of L. rhinoceros using five solvents demonstrated 44 constituents were identified. Compounds from the fatty acid group were the most predominant (68.58%) and the main constituent was linoleic acid (49.39%). This study also demonstrated that oral administration of L. rhinocerus did not noticeably show treatment-related signs of toxicity in both male and female rats. We also suggested that oral administration of L. rhinocerus extract did not result in remarkable teratogenicity in rats. The antiasthmatic potential of L. rhinoceros extract was further investigated on ovalbumin (OVA)-induced airway inflammation Sprague Dawley rats. Treatments with L. rhinocerus extract significantly ameliorated related asthmatic parameters in the induced rats. Specifically, L. rhinocerus extract comparatively reduced eosinophils numbers in BALF, lgE in serum, Th2 cytokines (IL-4, IL-5 and IL-13) levels in BALF, eosinophil infiltrations in the lungs as well as modulate regulatory T cell numbers in the airways. lmmunomodulatory effects of L. rhinocerus extract demonstrated improved splenocyte population mainly of co3•co4• and Co3•cos• as well as improved splenocytes proliferation and phagocytosis activity and controlled nitric oxide (NO) production. In conclusion, L. rhinocerus has the potential to be used as an alternative for the treatment of allergic asthma.